The Knowledge, Attitude and Practice of Fixed Prosthodontics: A Survey Among Dental Practitioners in Eastern Nepal - Rathi, A.; Jha, R. K.; Bhochhibhoya, A.; Guragain, M. (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: The aim of the study is to evaluate the knowledge, attitude and fixed prosthodontics practice guidelines amongst dental practitioners of Eastern part of Nepal.Materials and Methods: A descriptive cross‑sectional study was done among dental practitioners of Eastern Part of Nepal Practicing in Private Clinics and Dental Schools. A total of 250 dentists were selected randomly from private and public sectors and dental schools. A survey was conducted through a printed and online standard questionnaire with 18 open as well as multiple choice questions delivered to dental practitioners. All data were collected and coded, the statistical analysis was done using SPSS statistical software package. Descriptive statistics were used for data analysis.Result: The study showed that 167 (66.8%) were males while 83 (33.2%) were females. 80 (32%) of dentists were practicing crown and bridge for 1‑3 years, 88 (35.2%) of dentists were practicing crown and bridge for 4‑10 years, 38 (15.2%) of dentist were practicing for 11‑15 years while 44 (17.6%) of them were practicing for more than 16 years. Most of respondents 175 (70%) worked in private clinics. 90(36%) of participants fabricated study models before commencing fixed prosthodontic treatment. 190(76%) of participants always used radiographs for abutment tooth evaluation. Vitality test for restored abutments were always done by 115 (46%) respondents. Majority of respondents 200 (80%) were using high-speed hand pieces and diamond bur during preparation 130 (52%) While preparing of teeth for dental prosthesis. additional cured silicon was mostly used by most of the practitioners 110 (44%) for making final impression with a Putty and wash techniques 183 (73.2%).165 (66%) participants used wax for bite registration, 100 (40%) of respondents always used retraction cord and 08(43.2%) practitioners never give provisional crown and bridges. Both written prescriptions and verbal communications were used during communication between dentist and lab by 175 (70%) respondents.Conclusion: The dental practitioners of Eastern part of Nepal displayed acceptable level of knowledge and awareness regarding fixed prosthodontics practice. However, to further enhance efficiency and performance, an effort should be made to update the knowledge by conducting CDE on recent advances in dentistry and dental practices.